2021
DOI: 10.17582/journal.pjar/2021/34.1.23.28
|View full text |Cite
|
Sign up to set email alerts
|

Development and Growth: Influence of Sowing Dates on Performance of Cotton Cultivars

Abstract: C otton (Gossypium hirsutum L.) plant is recognized as white gold and warm humid area of the world under its cultivation (Meredith et al., 1997). In the world, Pakistan ranked 3 rd being a consumer and fourth in terms of production (GoP, 2015-16). It has a leading role in Pakistan's economy as a main cash crop.Moreover, foreign exchange earnings and support about 1.5 million rural economies (Hussain et al., 2010;Ahmad et al., 2009). Cotton crop share in value addition is 5.1 % and in gross domestic production … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…Sowing date have a big impact on cotton cultivars. The growth and developmental characteristics of late-sown cotton were significantly reduced (Ali et al, 2021).…”
Section: Resultsmentioning
confidence: 96%
“…Sowing date have a big impact on cotton cultivars. The growth and developmental characteristics of late-sown cotton were significantly reduced (Ali et al, 2021).…”
Section: Resultsmentioning
confidence: 96%
“…According to El Hassan [8] compared to later sowing dates, early sowing produced taller plants with higher LAI and more total dry weight in Sudan. The study conducted by Ali et al [9] included three planting dates: April 21, May 5, and May 20, the sowing date on May 5th yielded a greater leaf area index, but the sowing date April 21st produced higher TDM yield. The TDM accumulation per plant at all of stages in crop growth was affected by varying plant geometries, the increase in dry matter can be due to the higher availability of nutrients, resulting in increased plant height, leaf count, and leaf area.…”
Section: Introductionmentioning
confidence: 99%
“…This, in turn, enhances the production of photosynthates and their subsequent accumulation in the plant, the relative growth rate (RGR) based on the TDM accumulation per plant per day exhibited a slow pace during the initial 0 to 30 days after sowing (DAS), accelerated significantly during 61 to 90 DAS, and subsequently decelerated as observed by [13] . Ali et al [9] showed that 15 th April to 10 th May sown cotton gave maximum crop growth rate. Kaur et al [14] studied on three sowing dates (20 th April, 10 th May, and 30 th May) revealed that the crop growth rate (CGR) was greater for the cotton sown earlier 20 th April.…”
Section: Introductionmentioning
confidence: 99%